Pathology of pancreatic disorders in canines - Vandana Vijayachandran (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2005)
The present investigation was undertaken to evaluate the prevalence and nature of pathological conditions of the canine pancreas and to correlate these with the general post mortem lesions. A detailed systematic examination of 100 carcasses brought for autopsy during the period of investigation was conducted and the gross and histopathological lesions were studied in detail, classified and documented. The study has revealed the high prevalence of pancreatic disorders in canines to the tune of 72 per cent. It was found that the dogs between one to five years were the most commonly affected. Among the different breeds German shepherds were found to be the most susceptible to pancreatic disorders. Females were found to show a predisposition for pancreatic disorders. The weight and length of the pancreas was found to increase with age. Out of the 72 per cent cases, the pancreatic lesions were severe in 21 per cent of the cases, moderate in 20 per cent and mild in 31 per cent. The specific conditions encountered were pancreatitis, parasitic infection, abscessation, blood vessel proliferation, ductular adenoma, adenocarcinoma of acinar pancreas, duct obstruction due to squamous metaplasia and islet cell hyperplasia and hyalinisation. The other pathological conditions included atrophy, hypoplasia, vacuolar degeneration, lipomatosis, ductular changes like fibrosis, hyperplasia, congestion, haemorrhage, oedema, lymph stasis and islet changes like degeneration and necrosis. Correlation of the pancreatic lesions with general postmortem findings has brought into light the fact that many gastrointestinal disorders had concurrent pancreatic lesions and almost all cases of chronic hepatorenal system disorders, related pancreatic changes of the same severity were seen.